SmartSight: IoT-Based Smart Blind Stick With Weather Detection And Anti-Lost Function - Ainul Bahriah Mohd Khir,; Nur Farah Aina Ahmad Mazrullah,; Nurul Izzah Zahirah Che Kamarudin,; Berahim, Mazniha (Multidisciplinary Applied Research and Innovation, 2025)
People with vision impairment face challenges in detecting objects while walking. Although many blind sticks are available, none offer weather detection to help users be aware of weather conditions. The SmartSight project aims to build a smart blind stick that not only detects surrounding objects to prevent collisions but also includes features like water detection, anti-lost functionality, and emergency management. Additionally, a mobile application allows guardians to monitor users. SmartSight is designed specifically for the safety of people with vision impairments. The project follows the prototype model methodology, involving phases which is requirement, quick design, build prototype, user evaluation, refining prototype, and implementation and maintenance. Development of this project involves hardware like Arduino, sensors, buzzers, Global Positioning System (GPS), and Global System for Mobile Communications (GSM) modules, as well as software like Arduino IDE, Android Studio, and Firebase. Testing of is conducted using the Accessibility Assessment Checklist method, with feedback gathered via Google Forms. Findings show that users find both the prototype and mobile application user-friendly, convenient, and recommended to use.